Breastfeeding Symptom Resolution After Sequential Labial–Lingual Frenectomies: A Case Report - Raymond J. Tseng; Jessica Altemara; Sharon Smart (Case Reports in Pediatrics)
Conclusion: This single case study provides a valuable starting point for the exploration of which dysfunctional breastfeeding symptoms are associated with a labial tie versus lingual tie. Further research with larger samples is warranted to explore optimal treatment strategies for diverse parent–baby dyads experiencing breastfeeding difficulties, or whose access to lactation support services is limited.